Impact of Talent Management on Employee Performance in Construction Industry of Eastern Nepal - Timsina, Paribesh; Jha, Priyanka Kumari (Apex Journal of Business and Management, 2023)
The construction industry requires competent and skilled talent to achieve set milestones. Talent management is a human resource strategy designed to attract, develop, and retain manpower. This study aims to explore the impact of talent management on employee performance in the construction industry. The three factors of talent management strategies taken into consideration for this study are training and development, talent retention strategies, and performance management systems. A simple random sampling technique was used to distribute questionnaires to working professionals in Province 1. Linear regression analysis was used to find the correlation between talent management strategies and employee performance. The findings revealed that talent retention strategies and performance management systems significantly affect employee performance in the construction industry, while training and development moderately affect employee performance. The dependent variables were correlated with R2 values of 0.816, 0.793, and 0.549 for talent retention strategies, performance management systems, and training and development, respectively. All independent variables were correlated with an R2 value of 0.896. Succession planning, career development, management feedback, and employee appraisal were identified as key factors in achieving standard quality output in the construction industry. This study highlights the importance of talent management strategies in enhancing employee performance in the construction industry. The findings suggest that organizations should focus on talent retention strategies and performance management systems to improve employee performance.